2007
DOI: 10.1186/1471-2121-8-22
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation, transport, and complex formation of palmitoyl protein thioesterase 1 (PPT1) – distinct characteristics in neurons

Abstract: Background: Neuronal ceroid lipofuscinoses (NCLs) are collectively the most common type of recessively inherited childhood encephalopathies. The most severe form of NCL, infantile neuronal ceroid lipofuscinosis (INCL), is caused by mutations in the CLN1 gene, resulting in a deficiency of the lysosomal enzyme, palmitoyl protein thioesterase 1 (PPT1). The deficiency of PPT1 causes a specific death of neocortical neurons by a mechanism, which is currently unclear. To understand the function of PPT1 in more detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 51 publications
10
54
0
Order By: Relevance
“…Western blotting with an anti-PPT1 antibody confirmed a similar migration pattern for hPPT1 protein in transfected cell lysates (Figure 3D, bottom panel). These data indicate that both ABC34 ( 13 ) and ABC45 react with PPT1 and are consistent with previous studies demonstrating that this enzyme is glycosylated (Camp et al, 1994; Lyly et al, 2007). In contrast, FP-Rh failed to detect hPPT1 in transfected cell lysates (Figure 3D).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Western blotting with an anti-PPT1 antibody confirmed a similar migration pattern for hPPT1 protein in transfected cell lysates (Figure 3D, bottom panel). These data indicate that both ABC34 ( 13 ) and ABC45 react with PPT1 and are consistent with previous studies demonstrating that this enzyme is glycosylated (Camp et al, 1994; Lyly et al, 2007). In contrast, FP-Rh failed to detect hPPT1 in transfected cell lysates (Figure 3D).…”
Section: Resultssupporting
confidence: 92%
“…(D) Verification that recombinant human PPT1 expressed by transient transfection in HEK293T cells reacts with ABC45 (1 µM), but not FP-Rh (1 µM), and the ABC45 reactivity is blocked by ABC34 (5 µM, 4 h). PNGaseF treatment causes a shift in PPT1 signals by SDS-PAGE, consistent with the reported glycosylation state of this protein (Camp et al, 1994; Lyly et al, 2007). Upper, ABPP gel; lower, anti-PPT1 western blot.…”
Section: Figuresupporting
confidence: 87%
“…In addition to an MPR-independent route, Cathepsin D can also use the classical MPR pathway for its lysosomal trafficking [Canuel et al, 2008;Kornfeld and Mellman, 1989;von Figura and Hasilik, 1986]. Palmitoyl protein thioesterase 1 (PPT1/CLN1), the protein defective in the infantile NCL, has also been reported to show properties that differ from those involved in the classical MPRmediated sorting [Lyly et al, 2007]. Interestingly, we have recently shown that PPT1/CLN1 interacts with CLN5, and furthermore, can facilitate the trafficking of the mutated CLN5 from the ER to the lysosomes [Lyly et al, 2009].…”
Section: Discussionmentioning
confidence: 98%
“…The glycan moieties are endoglycosidase H sensitive, demonstrating that PPT1 possesses only N-type glycosylation. Proper glycosylation is required for the stability and activity of the enzyme 30 and glycosylation site mutants of PPT1 have greatly reduced enzyme activity 44 . Interestingly, despite localization of PPT1 in lysosomes, its enzymatic activity is optimal at neutral pH not pH 4-5 40 (data not shown).…”
Section: Discussionmentioning
confidence: 99%